A Restorative Justice System in Indonesia: A Close View from the Indigenous Peoples' Practices - Nur Rochaeti; Mujiono Hafidh Prasetyo; Umi Rozah; Jihyun Park (Sriwijaya Law Review, 2023)
The Indonesiancrime rate until May 2020 increased due to public orders and crime disturbances in the last 22 weeks.Data from correctional institutions in February 2021 showed that some regional offices were over capacity while others were normal. The 1945 IndonesianConstitution recognises traditional institutions in the criminal justice system and requires judges to consider legal values and a sense of justice in society. This study aims to determine Indonesia's customary criminal justice system as a form of restorative justice. This research used a socio-legal approach and found that public participation in Indonesia, through customary groups, can help prevent crime and solve problems through discussion and following applicable customary law processes. As a result, Indonesian researchers have regulated and recognised customary justice's existence and implemented it to deal with cases in their environment. Restorative justice is a criminal mechanism that aims to restore the relationship of the conflicting parties to the state before the conflict and is carried out informally. This concept is also an acknowledgement of oriental legal philosophy which, in resolving any conflict, always seeks to restore relations; macro stability or society can even affect the stability of the universe. The practice of Restorative Justice occurs in customary law. As a legal philosophy, the legal policy of implementing Restorative justice should be interpreted mainly as revitalising customary law if conflicts occur between fellow supporters of the same customary law. The settlement of cases in the Baduy community is straightforward. The settlement prioritises forgiving each other. Restorative justice is performed by combining criminal justice mechanisms with public participation in a discussion mediation.